Charge transport mechanism in bis (double-decker lutetium(III) phthalocyanine) (Lu2Pc4) thin film - (:unkn) unknown (ELSEVIER SCIENCE SA, 2005)
The dc and ac dark conductivity measurements have been performed on spin-coated Lu2Pc4 thin film in the frequency range 40-10(5) Hz and in the temperature range 50-290 K. Measurements revealed that dc behaviour of the film can be described by Mott's three-dimensional variable range hopping (VRH) model, T-1/4 law, in the whole temperature range. The ac conductivity alpha(omega) varied as omega(s), where the exponent s is found temperature dependent variable and always less than unity. The measured ac conductivity data are discussed in terms of classical models based on pair approximation and a unified theory. Although the ac behaviour can be approximately explained by the correlated barrier hopping model below the 190 K, the temperature dependencies are stronger than any classical model predicts. The log-log plot of the normalized conductivity sigma(omega)/sigma(0) with reduced frequency omega/sigma(0) showed that, the ac conductivity data agrees fairly well with the predictions of the extended pair approximation (EPA) model due to Summerfield and Butcher. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: ac conductivity; variable range hopping; lutetium phthalocyanine; EPA; FIELD-EFFECT TRANSISTORS; SUBSTITUTED PHTHALOCYANINES; ELECTRICAL-PROPERTIES; CONDUCTIVITY; AC; SEMICONDUCTORS; DEVICES; DC